Elemen dan Komposisi Fasad Bangunan Berlanggam Indies Empire di Kawasan Pusat Kota Probolinggo - Kusumawardani, Safira (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
This research aims to apply theory regarding the elements and composition of Indies Empire style building facades in the central area of Probolinggo City. The analytical method used is a qualitative descriptive method. The research results show that the type of roof used is dominated by shield roofs. The floor in every building has a level of at least one level from the ground. The walls use brick material and are dominated by white paint finishing. The columns on the terrace are arranged single and double. The doors and windows have double leaves made of wood. The signs found include names and symbols. Then, ornaments are found on most buildings, especially on the roof and openings. Meanwhile, the balance found is symmetry. There is a rhythm formed from repetition on the facade. The center of attention is located in the center of the building. The scale of the building is dominated by a monumental scale. The sequence that occurs in the research object building is regular. The unity of the building is mostly intact and harmonious.